PENCEGAHAN RADIKALISME BAGI REMAJA TINGKAT SEKOLAH MENENGAH ATAS DI MAN PURBALINGGATER - Fetri Fatorina; Mukhlisin Mukhlisin; Chamid Sutikno (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2022)
Knowledge of qualified religious insights and strong general knowledge is a solid provision not to be exposed to radicalism. In fact, the religious insights taught in schools are not sufficient to ward off the spread of radicalism among adolescents at the high school level. So what efforts should be made to maximize efforts to counteract radicalism in high school adolescents? The purpose of this service is to contribute to preventing the spread of radicalism among high school adolescents. The method of implementing community service is carried out in several stages such as the stages of observation, coordination, preparation, implementation, reporting and publication. Based on the results of community service that has been carried out, it is found that the efforts that must be made in order to prevent the spread of radicalism are through strengthening religious insight through teachers who have a clear sense, strengthening the spirit of patriotism and nationalism through extracurricular activities and classroom learning, and not forgetting mentoring. From the teachers and parents regarding the reading and socializing of these teenagers